Koleksi Surat Kabar Langka Perpustakaan Nasional RI sebagai sumber informasi sejarah Indonesia pada masa revolusi (1949-1950): Studi Kasus Surat Kabar Berita Indonesia, Al-Djihad dan Ra’jat - Supratman, Frial Ramadhan (Jurnal Tadwin, 2022)
Newspaper is one of non-book library collection which is important in delivering information. National Library of Indonesia is a library whose the largest newspaper collection in Indonesia. One of the most prominent collection in the library is Indonesian newsapaper published during revolution period (1949-1950). Many of which published during revolution period has given abundance information about condition in Indonesia, including diplomacy and struggle activity. This article explains information literacy regarding Indonesian history during revolution. This research was conducted using a qualitative method using a descriptive and historical approach through field observations of the collection of Indonesian newspapers published during the revolution at the National Library of the Republic of Indonesia. Author focuses on explaining the National Library of Indonesia’s rare newspaper collection published during revolution period (1949-1950).